David Foster Wallace and Repressive Taboos: Clenette Henderson, yrstruly and the identity politics of representation - Matthew Alexander (Forum, 2017)
David Foster Wallace’s use of disenfranchised voices in Infinite Jest (1996) receives little critical attention. Clenette Henderson and yrstruly’s narratives raise issues of taboo subjects: child sexual abuse, drug-addiction, and prostitution. A close reading of their voices aims to break over twenty years of critical silence by exposing such taboos.